Living between science and belief : the modern dilemma - Villa-Vicencio, Charles (SUN MeDIA, 2021)
"Most thoughtful people live in an interregnum between science and religion. Traditional religious answers concerning the beginning, purpose, and end of life are questioned by the natural sciences, with neuroscience conceivably constituting the last frontier where skeptics and believers explore common ground. The question concerns the nature of reflective and creative moments in life. Can these be reduced to the intersect between the nerve cells and molecules of the physical brain? Does this account for the human sense of mystery, or even spirituality? Is there a nexus between the physical and unknown dimensions of existence? The mutation in the history of theism suggests that progressive theology in the West may be set for further change."--Publisher.